2007
DOI: 10.1214/088342306000000673
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Population Dynamics Models in Inference

Abstract: Increasing pressures on the environment are generating an ever-increasing need to manage animal and plant populations sustainably, and to protect and rebuild endangered populations. Effective management requires reliable mathematical models, so that the effects of management action can be predicted, and the uncertainty in these predictions quantified. These models must be able to predict the response of populations to anthropogenic change, while handling the major sources of uncertainty. We describe a simple `… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 67 publications
0
110
0
Order By: Relevance
“…Simulations that contained both process and observation error were used to assess the validity of this assumption. We found that the methodology was robust to violations of the assumption of no observation error (see SI Text and Table S1 for details), thus obviating the need for a more sophisticated approach of fitting a model with both types of noise (33,34). Further studies are needed to assess the robustness of our findings to more realistic stochasticity and observation error (36).…”
Section: Methodsmentioning
confidence: 82%
“…Simulations that contained both process and observation error were used to assess the validity of this assumption. We found that the methodology was robust to violations of the assumption of no observation error (see SI Text and Table S1 for details), thus obviating the need for a more sophisticated approach of fitting a model with both types of noise (33,34). Further studies are needed to assess the robustness of our findings to more realistic stochasticity and observation error (36).…”
Section: Methodsmentioning
confidence: 82%
“…Fecundity (average number of females produced per female, f ) was set at 2.6, juvenile survival (survival from birth until 1 yr old, / juv ) at 0.2 and adult survival (annual survival after 1 yr of age, / ad ) at 0.5. The expected number of individuals in the two age classes at time t þ 1 is given by the product of the population vector (containing the number of individuals) in year t and the projection matrix (Caswell 2001, Buckland et al 2007 as…”
Section: Methodsmentioning
confidence: 99%
“…Estimation of density and habitat relationships may also be combined in a single analysis (Hedley et al 2004, Royle et al 2004, Johnson et al 2010, Niemi & Fernández 2010. Inference about population processes is improved when combined with an observation model into a single likelihood framework (Goodman 2004, Buckland et al 2007, Royle & Dorazio 2008.…”
Section: Discussionmentioning
confidence: 99%